Antihypertensive efficacy of olmesartan medoxomil and candesartan cilexetil in achieving 24-hour blood pressure reductions and ambulatory blood pressure goals - Hans R. Brunner; Kikuo Arakawa (Кардиоваскулярная терапия и профилактика, 2011)
Background. For patients with hypertension, effective 24-hour blood pressure (BP) control is vital to ensure protection against the early morning surge in BP and the associated increased risk of cardiovascular events. The aim of this analysis was to assess the 24-hour antihypertensive efficacy of olmesartan medoxomil (20 mg once daily) compared with candesartan cilexetil (8 mg once daily), with particular emphasis on BP control during the early morning period. Methods. This is an additional analysis of a previously reported randomised, double-blind study in which 635 patients with mainly mild to moderate hypertension were randomised to 8 weeks of treatment with either olmesartan medoxomil 20 mg/day or candesartan cilexetil 8 mg/day. Changes from baseline during the last 4 and 2 hours of ambulatory BP measurement (ABPM) after 1, 2 and 8 weeks of treatment were compared between the two groups. In addition, the proportions of patients who achieved various ABPM goals, including those suggested by the European Society of Hypertension/European Society of Cardiology (ESH/ESC) [<125/80 mm Hg] and the Japanese Society of Hypertension (JSH) [<135/80 mm Hg], over 24 hours, during the daytime and at the last 4 and 2 hours of ABPM measurement were also compared. Results. After 8 weeks, significantly greater proportions of patients treated with olmesartan medoxomil 20 mg achieved 24-hour and daytime ABPM goals recommended by the guidelines of the ESH/ESC (25,6 % and 18,3 %, respectively) and JSH (37,5 % and 26,6 %, respectively) compared with candesartan cilexetil 8 mg (24-hour ESH/ESC goal 14,9 %, p<0,001; 24-hour JSH goal 26,6 %, p=0,003; daytime ESH/ESC goal 9,6 %, p=0,002; daytime JSH goal 16,4 %, p=0,002). During the last 4 hours of 24-hour ABPM, the proportions of patients who achieved the ESH/ESC and JSH ABPM goals were significantly greater with olmesartan medoxomil (33,3 % and 39,1 %, respectively) than with candesartan cilexetil (22,9 %, p<0,001 and 31,6 %, p=0,047, respectively). Similarly, during the last 2 hours of 24-hour ABPM, the proportions of patients who achieved these BP goals were either significantly greater (JSH) or approached statistical significance (ESH/ESC) with olmesartan medoxomil (26,9 % and 19,9 %, respectively), compared with candesartan cilexetil (19,6 %, p=0,028 and 14,3 %, p=0,061, respectively). Conclusion. Compared with candesartan cilexetil 8 mg, greater proportions of olmesartan medoxomil-treated patients (20 mg) achieved ESH/ESC and JSH ABPM goals over 24 hours. The superior BP control of olmesartan medoxomil was also reflected in the larger proportions of olmesartan medoxomil-treated patients who achieved the ESH/ESC and JSH ABPM goals during the early morning surge period. This not only demonstrates that olmesartan medoxomil 20 mg provides superior 24-hour BP reduction, but also suggests that olmesartan medoxomil may provide greater protection against the increased risk of cardiovascular events associated with the early morning BP surge period.